2018
DOI: 10.1186/s12888-018-1702-2
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia as an independent predictor of suicide attempts: a nationwide population-based retrospective cohort study

Abstract: BackgroundNumerous studies have verified that insomnia is associated with suicidal ideation, suicide attempts, and death by suicide. Limited population-based cohort studies have been conducted to examine the association. The present study aimed to analyze whether insomnia increases the risk of suicide attempts and verify the effects of insomnia on suicide risk.MethodsThis study is a cohort study using 2000–2013 hospitalization data from the National Health Insurance Research Database (NHIRD) to track the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Pooled results from logistic regression analyses with estimated odds ratio (OR) and 95% confidence interval (CI) for all-cause and cause-specific mortality within 2 years after collecting a first prescription of hypnotics between January 2005 and December 2015, compared with subjects who never collected prescriptions of hypnotics concluded that insomnia increases the risk of incident depression (Fang, Tu, Sheng, & Shao, 2019) and suicide (Bjorngaard, Bjerkeset, Romundstad, & Gunnell, 2011;Lin, Lai, & Perng, 2018).…”
Section: Ta B L Ementioning
confidence: 99%
“…Pooled results from logistic regression analyses with estimated odds ratio (OR) and 95% confidence interval (CI) for all-cause and cause-specific mortality within 2 years after collecting a first prescription of hypnotics between January 2005 and December 2015, compared with subjects who never collected prescriptions of hypnotics concluded that insomnia increases the risk of incident depression (Fang, Tu, Sheng, & Shao, 2019) and suicide (Bjorngaard, Bjerkeset, Romundstad, & Gunnell, 2011;Lin, Lai, & Perng, 2018).…”
Section: Ta B L Ementioning
confidence: 99%
“…Recent studies reported that somatic symptoms such as insomnia are associated with suicide [43,44]. In addition, receiving benzodiazepines may be associated with increased aggression [45] and may result in disinhibition [46], which may be the factors that contribute to suicidal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, insomnia has been shown to have prognostic validity for the development of posttraumatic stress disorder (PTSD) [6,8] and depression [9,10]. Moreover, the already high vulnerability for suicidal behavior in individuals with mental health problems is further increased in those with poor sleep [11,12]. Thus, early and adequate treatment of sleep disorders in individuals with mental disorders may be of paramount importance, and might well lead to better mental health outcomes and improved quality of life.…”
Section: Introductionmentioning
confidence: 99%